INQUIRY-BASED LEARNING MANAGEMENT INCORPORATING ARGUMENTATION TECHNIQUES WITH FAKE NEWS CONTEXTS TO DEVELOP COMPETENCY IN RESEARCHING, EVALUATING AND USING SCIENTIFIC INFORMATION FOR DECISION-MAKING AND ACTION IN DNA TECHNOLOGY AMONG MATHAYOMSUKSA 4 STUDENTS - Khongtak, Thani; Bongkotphet, Thitiya (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
This classroom action research aimed to establish the guidelines and to examine the effects after the implementation of the inquiry-based learning management incorporating argumentation techniques with fake news contexts to develop competency in researching, evaluating and using scientific information for decision-making and action in DNA Technology. The target group consisted of 28 students in Mathayomsuksa 4 during the second semester of the 2024 academic year from a medium-sized school in Phichit Province. The research instruments included lesson plans, learning reflection forms, investigation reports, and assessment forms regarding competency in researching, evaluating and using scientific information for decision-making and action. Data were analyzed using content analysis, mean, and percentage. The research results revealed that: 1) The guidelines for managing inquiry-based learning incorporating argumentation techniques in fake news contexts to develop competency in researching, evaluating and using scientific information for decision-making and action are proposed. This includes the use of fake news related to content and issues of public interest to encourage learners to researching information from credible sources to support their arguments. Subsequently, argumentation activities should be employed to facilitate the exchange of learning, synthesis of learning, and informed decision-making regarding disputed issues in fake news and 2) The development of competency in researching, evaluating and using scientific information for decision-making and action showed an overall improvement both during and after the learning process (from low to moderate levels).